Preparation method of all-metal-coated special-shaped metal matrix diamond composite material
Through the preparation method of all-metal coated special-shaped metal foundation diamond composite material, the problem of difficulty in preparing special-shaped parts with high thermal conductivity and low thermal expansion coefficient is solved in the prior art, and an efficient and low-cost preparation process is achieved, which is suitable for the heat dissipation needs of electronic devices.
Patent Information
- Application Number
- CN202210599510.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-30
- Publication Date
- 2025-05-27
- Estimated Expiration
- 2042-05-30
AI Technical Summary
The existing metal base diamond composite preparation methods are difficult to prepare special-shaped parts with high thermal conductivity and low thermal expansion coefficient, and are difficult to process and costly, which cannot meet the heat dissipation needs of electronic devices.
The preparation method of all-metal coated special-shaped metal base diamond composite material is adopted, and the shape of metal foil tape is engraved through a lettering machine, diamond particles and metal powder are laid, and multi-layered pre-pressing and hot-pressing sintering are carried out to form a high-density composite material.
The preparation of metal-based diamond composite materials with high thermal conductivity and low thermal expansion coefficient is easy to process and low cost, suitable for heat dissipation applications of electronic devices.
Smart Images

Figure CN115592119B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and particularly relates to a preparation method of a metal matrix diamond composite material. Background Art
[0002] With the continuous development of the trend of miniaturization, integration and high power of electronic devices in the fields of aerospace, communication, etc., the rapidly increasing heat flux poses a huge challenge to device heat dissipation. Excessive temperature has become an important factor for reducing the lifespan and performance failure of electronic devices. Diamond is the material with the highest thermal conductivity (600 - 2200 W·m -1 ·K -1 ) in nature, and has a low coefficient of thermal expansion (1.0×10 -6 K -1 ) and a low density (3.52 g / cm 3 ). Therefore, diamond can be combined with metals such as copper and aluminum as a reinforcement phase to obtain a thermal conductive composite material with high thermal conductivity and low coefficient of thermal expansion. The metal matrix diamond high thermal conductivity composite material has a higher thermal conductivity and a lower coefficient of thermal expansion than the traditional first-generation W-Cu and second-generation SiC-Al composite heat sink materials, and has more excellent heat dissipation performance, and can be applied to many fields such as integrated heat sinks, laser diode heat dissipation substrates, IGBT substrates, LED heat sinks, etc. For some of these application scenarios, special-shaped parts are required, and the existing preparation methods of metal matrix diamond composite materials are difficult to achieve low-cost and simple preparation of easily machined special-shaped parts.
[0003] The preparation methods of metal matrix diamond composites are divided into powder metallurgy method and liquid phase method. The powder metallurgy method mainly includes hot press sintering, spark plasma sintering and hot isostatic pressing sintering. Among them, only hot press sintering is suitable for industrial mass production and has a relatively low cost. The process of hot press sintering is as follows: first, fill the dry powder into the mold, and then apply unidirectional pressure to the mold while heating. Under the simultaneous action of temperature and pressure, the metal powder is in a thermoplastic state. A certain pressure can promote particle rearrangement and plastic flow between particles, and high-density composites can be prepared. The liquid phase method mainly includes pressure infiltration, pressureless infiltration and squeeze casting. The composites prepared by pressure infiltration have a high relative density, a high temperature, a sufficient reaction time, and a good interface bonding of the composites. However, it also brings problems such as diamond graphitization and the rupture of diamond caused by impurities in synthetic diamond at high temperatures, resulting in a decrease in thermal conductivity. More importantly, the equipment investment and mold cost of this preparation process are relatively high, the production cycle is long, and the production cost is high, which is suitable for scientific research and small batch production. Pressureless infiltration has high requirements for wettability, and it is difficult to control the interface bonding of the composites. The pressure applied by the squeeze casting method is relatively large, so the production time is short, and infiltration can be completed within a few minutes, and the process stability is good. However, its disadvantage is that it requires high-pressure equipment and high-pressure-resistant molds with good sealing, so the production cost is relatively high, and there are great limitations in the production of parts with complex shapes. To sum up, hot press sintering is suitable for industrial mass production, and metal matrix diamond composites with good performance can be prepared under the action of lower temperature and smaller pressure.
[0004] However, hot press sintering is limited by its unidirectional pressing method and can only prepare circular or square cake-shaped products. Moreover, the powder metallurgy method is mostly used to prepare metal matrix diamond composites by hot press sintering, that is, first mix the metal powder and diamond particles evenly, and then place them in a hot press sintering furnace for sintering. It is impossible to form special-shaped parts in one step. Even if the sintered parts are cut into special-shaped parts by means of laser cutting, etc., the remaining diamond particles are difficult to recycle, and the cost of preparing special-shaped parts is high. In addition to the great difficulty in preparation, the metal matrix diamond composite special-shaped parts also have the problem of great processing difficulty. Diamond has extremely high hardness, while metal copper or aluminum is relatively soft, resulting in the difficulty of grinding and polishing metal matrix diamond composites. Only diamond materials can be used for grinding and polishing metal matrix diamond composites, which not only has a high cost, low processing efficiency, but also has low processing accuracy and rough surface, making it difficult to meet the requirements of actual applications. For the application scenarios of metal matrix diamond heat sink materials, the packaging substrate material needs to perform metal plating and other treatments on the metal matrix diamond composites, so there are certain requirements for the surface roughness of the materials. At present, the surface roughness of diamond-copper or diamond-aluminum composites after grinding and polishing is difficult to meet the requirements, which greatly limits the use of metal matrix diamond composites in the field of electronic packaging. The existing technologies pay less attention to the easy processability and the preparation of special-shaped parts of metal matrix diamond composites, or the processes are complex and the costs are high. Summary of the Invention
[0005] The object of the present invention is to provide a method for preparing a fully metal-coated special-shaped metal-based diamond composite material, which can regulate the distribution of diamond and metal in the single-layer composite material, prepare a metal-based diamond composite material with high thermal conductivity, easy processing and complex shape, and the surface of the obtained special-shaped part is fully metal-coated, changing the processing of the original metal-based diamond into the processing of metal, which can ensure low surface roughness, simple equipment, strong operability and repeatability.
[0006] To achieve the above object, the following technical solutions are adopted:
[0007] A method for preparing a fully metal-coated special-shaped metal-based diamond composite material, comprising the following steps:
[0008] (1) Use a cutting plotter to engrave the shape of each cross-section of the special-shaped part on the release paper of the circular metal foil tape, and tear off the release paper in the engraved special-shaped part area;
[0009] (2) Use a diamond cloth spreader to evenly spread the diamond particles containing the coating on the special-shaped part area of the metal foil tape, then tear off the release paper in the non-special-shaped part area, and evenly spread aluminum powder or copper powder on the metal foil tape with a cloth spreader to obtain a metal-based diamond composite thin sheet;
[0010] (3) Stack the obtained composite thin sheets in multiple layers and pre-press to obtain a metal-based diamond composite material preform;
[0011] (4) Place the obtained composite material preform in a hot press furnace, and hot press and sinter it into shape under a vacuum environment, and cut to obtain a fully metal-coated special-shaped metal-based diamond composite material.
[0012] According to the above scheme, the metal foil tape described in step 1 is composed of a metal base layer, a pressure-sensitive adhesive and a release paper; the thickness is 0.06-0.2 mm, preferably 0.08-0.15 mm; the diameter is 10-500 mm, preferably 80-200 mm; the metal base layer is aluminum or copper with a purity higher than 99.95 wt%.
[0013] According to the above scheme, in step 1, the size and shape information of each cross-section of the special-shaped part is input into the cutting plotter through a computer to obtain the metal foil tape with the engraved shape of each cross-section.
[0014] According to the above scheme, the diamond particles described in step 2 are artificial diamond or natural diamond, and the particle size is 40-500 μm, preferably 100-300 μm.
[0015] According to the above scheme, the coating described in step 2 is one of SiC-Si, TiC-Ti, Cr 3 C 2 -Cr, WC-W prepared by the vacuum evaporation coating method, and the coating thickness is 0.01-0.1 μm.
[0016] According to the above solution, the particle size of the copper powder or aluminum powder described in step 2 is 20 - 300 μm, preferably 80 - 200 μm.
[0017] According to the above solution, the pre - pressing pressure in step 3 is 5 - 50 MPa, and the pressure - holding time is 1 - 10 min; preferably, the pressure is 30 MPa and the pressure - holding time is 5 min; the thickness of the preform is 0.2 - 5 mm, preferably 1 - 2 mm.
[0018] According to the above solution, when the composite material preform described in step 4 uses aluminum as the metal matrix, the hot - pressing sintering process conditions are as follows:
[0019] The vacuum degree ≤ 10 Pa; the heating program is to rise at 2 - 10 °C / min to 300 - 500 °C and hold for 0.5 - 2 h, then rise at 5 - 20 °C / min to 600 - 750 °C and hold for 30 - 90 min; the pressure program is not to apply pressure before sintering, apply pressure of 5 - 20 MPa at 500 - 600 °C, and apply pressure of 5 - 50 MPa at the highest sintering temperature.
[0020] According to the above solution, when the composite material preform described in step 4 uses copper as the metal matrix, the hot - pressing sintering process conditions are as follows:
[0021] The vacuum degree ≤ 10 Pa; the heating program is to rise at 2 - 10 °C / min to 300 - 500 °C and hold for 0.5 - 2 h, then rise at 5 - 20 °C / min to 850 - 1200 °C and hold for 30 - 90 min; the pressure program is not to apply pressure before sintering, apply pressure of 5 - 20 MPa at 500 - 600 °C, and apply pressure of 5 - 50 MPa at the highest sintering temperature.
[0022] According to the above solution, the cutting in step 4 is laser cutting or wire - electrical - discharge cutting; after cutting, it also includes rough grinding, fine grinding, and polishing of the special - shaped parts to achieve a surface finish of Ra ≤ 0.4 μm.
[0023] In the present invention, first, a special - shaped part shape is engraved on the release paper of the aluminum foil or copper foil tape by a lettering machine, then diamond particles with a coating are evenly spread on the special - shaped part area of the metal foil tape, and then aluminum powder or copper powder is evenly laid to form a metal - based diamond composite thin sheet. The composite thin sheets are stacked in multiple layers and pre - pressed into a preform with a thickness of 0.2 - 5 mm. Then, by controlling the hot - pressing sintering process, a metal - based diamond composite material with high density is obtained. Finally, through machining, the metal copper or aluminum around the special - shaped part is cut to obtain a metal - based diamond special - shaped part with high thermal conductivity and low coefficient of thermal expansion.
[0024] To ensure the simple preparation of special-shaped parts, the present invention uses a cutting plotter to precisely engrave the shape of the special-shaped parts on the release paper of the metal foil tape; to ensure the machinability and good surface finish of the metal-based diamond, the metal foil tape is used so that the upper and lower surfaces and the surrounding of the special-shaped parts are all metal; to ensure the shape of the special-shaped parts, copper powder or aluminum powder of different particle sizes is added, and the shape of the special-shaped parts is maintained by the height difference of the thermal expansion coefficients and particle sizes of the metal powder and diamond; to obtain a metal-based diamond composite material with high thermal conductivity, a pre-pressing process is used in combination with a special heating program and pressing program to fix the position of the diamond particles, avoid the drift of the diamond particles, and at the same time keep warm at a certain temperature to remove the pressure-sensitive adhesive on the metal foil tape and reduce impurities.
[0025] The present invention has excellent machinability for metal-based diamond composite materials with complex shapes. The diamond and metal are evenly arranged, and the diamond surface coating improves the interfacial bonding property. By adjusting the thickness of the metal foil, the particle sizes of the diamond and metal powder, a special-shaped metal-based diamond part with adjustable thermal conductivity and thermal expansion coefficient is precisely prepared. The aluminum-based diamond composite material prepared by the present invention has a thermal conductivity TC≥300 (W / mK), a thermal expansion coefficient CTE≤5.0 (10 -6 / K), and a surface roughness Ra≤0.4μm; the copper-based diamond composite material has a thermal conductivity TC≥400 (W / mK), a thermal expansion coefficient CTE≤6.0 (10 -6 / K), and a surface roughness Ra≤0.4μm; it has broad application prospects and practical value.
[0026] Compared with the prior art, the beneficial effects are as follows:
[0027] 1) The preparation process is simple and can be industrially promoted;
[0028] 2) The prepared metal-based diamond composite material is a special-shaped part, meeting the requirements of certain application scenarios, integrally formed, and does not require multiple processing procedures;
[0029] 3) The surface layer of the prepared metal-based diamond composite material is completely covered with metal, only the metal area needs to be cut and polished, the processing difficulty is low, and the surface roughness is low, meeting the requirements of subsequent plating processing of the packaging material for electronic components;
[0030] 3) The diamond volume fraction and sample thickness of the prepared metal-based diamond composite material can be adjusted, the thermal conductivity is high, the thermal expansion coefficient is small, and the thermal conductivity and thermal expansion coefficient can be adjusted, meeting the performance requirements of heat dissipation materials for different application scenarios. Description of the Drawings
[0031] Figure 1 : Process flow chart for the preparation of the aluminum-based diamond composite material of the present invention;
[0032] Figure 2 : Schematic diagram of the diamond cloth in the special-shaped area of the aluminum foil tape in Example 1;
[0033] Figure 3 : Macroscopic photograph of the cutting of the diamond-aluminum special-shaped part prepared in Example 1;
[0034] Figure 4 : Microscopic cross-sectional photograph of the diamond-copper special-shaped part prepared in Example 2. Detailed implementation manners
[0035] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below in conjunction with embodiments.
[0036] A preparation method of a fully metal-coated special-shaped metal-based diamond composite material is provided in the detailed implementation manners:
[0037] (1) Use a cutting plotter to engrave the shape of each cross-section of the special-shaped part on the release paper of the circular metal foil tape, and tear off the release paper of the engraved special-shaped part area; the metal foil tape is composed of a metal base layer, a pressure-sensitive adhesive, and a release paper; the thickness is 0.06 - 0.2 mm, preferably 0.08 - 0.15 mm; the diameter is 10 - 500 mm, preferably 80 - 200 mm; the metal base layer is aluminum or copper with a purity higher than 99.95 wt%.
[0038] The cutting plotter is a general computer cutting plotter on the market. Users can input the size and shape information of each cross-section of the special-shaped part into the cutting plotter through a computer, and the cutter of the cutting plotter is controlled and driven by the computer to engrave the desired shape on the release paper of the metal tape, keeping the metal substrate intact.
[0039] (2) Use a diamond cloth machine to evenly spread the diamond particles with a coating on the special-shaped part area of the metal foil tape, then tear off the release paper of the non-special-shaped part area, and evenly spread aluminum powder or copper powder on the metal foil tape with a cloth machine to obtain a metal-based diamond composite thin sheet; the diamond particles are artificial diamond or natural diamond, with a particle size of 40 - 500 μm, preferably 100 - 300 μm; the coating is one of SiC-Si, TiC-Ti, Cr 3 C 2 -Cr, WC-W prepared by vacuum evaporation coating method, and the coating thickness is 0.01 - 0.1 μm; the particle size of the copper powder or aluminum powder is 20 - 300 μm, preferably 80 - 200 μm.
[0040] Without adding aluminum powder or copper powder, only diamond adheres to the single-layer metal tape. During the sintering process, the diamond will drift outward, and the shape of the special-shaped part will change. After adding copper powder or aluminum powder with an appropriate particle size, during the heating-up process of sintering, the metal powder expands due to heat, restricting the drift of the diamond. Here, the selection of the particle size of the metal powder is very important and needs to be matched according to the particle size of the diamond. The principle is that the particle size of the metal powder is 70-80% of the particle size of the diamond, and the shape of the metal powder is preferably spherical. The use of the diamond distributor (Patent CN213439170U) in this step ensures that there is only a single layer of diamond particles on each layer of the metal tape, without the accumulation of diamond particles, which is beneficial to maintaining the shape of the special-shaped part and obtaining high density and thermal conductivity.
[0041] (3) Stack the obtained composite thin sheets in multiple layers and pre-press them to obtain a preform of the metal matrix diamond composite material; the pre-pressing pressure is 5-50 MPa, and the pressure holding time is 1-10 min; preferably, the pressure is 30 MPa and the pressure holding time is 5 min; the thickness of the preform is 0.2-5 mm, preferably 1-2 mm.
[0042] After pre-pressing, the diamond particles are embedded in the metal tape, fixing the position of the diamond and making it not easy to drift during the sintering process. The pre-pressing pressure should not be too large, otherwise the diamond particles will generate micro-cracks, affecting the thermal conductivity.
[0043] (4) Place the obtained composite material preform in a hot press furnace and hot press and sinter it into shape under a vacuum degree ≤ 10 Pa, and cut it to obtain a fully metal-coated special-shaped metal matrix diamond composite material. The cutting is laser cutting or wire electrical discharge machining; after cutting, the special-shaped part is further rough-ground, fine-ground, and polished to achieve a surface finish Ra ≤ 0.4 μm.
[0044] In the specific implementation manner, due to the different melting points of aluminum and copper, the hot press sintering process conditions for the obtained composite material preform are also different.
[0045] When the composite material preform uses aluminum as the metal matrix (aluminum foil tape and adding metal aluminum powder), the hot press sintering process conditions are as follows:
[0046] The vacuum degree ≤ 10 Pa; the heating program is to raise the temperature to 300-500 °C at a rate of 2-10 °C / min and hold for 0.5-2 h, and then raise the temperature to 600-750 °C at a rate of 5-20 °C / min and hold for 30-90 min; the pressure program is not to apply pressure before sintering, apply pressure of 5-20 MPa at 500-600 °C, and apply pressure of 5-50 MPa at the highest sintering temperature.
[0047] When the composite material preform uses copper as the metal matrix (copper foil tape and adding metal copper powder), the hot press sintering process conditions are as follows:
[0048] The degree of vacuum ≤ 10 Pa; the heating program is to increase the temperature from 2 - 10 °C / min to 300 - 500 °C and keep it warm for 0.5 - 2 h, then increase the temperature from 5 - 20 °C / min to 850 - 1200 °C and keep it warm for 30 - 90 min; the pressure program is not to apply pressure before sintering, apply pressure of 5 - 20 MPa at 500 - 600 °C, and apply pressure of 5 - 50 MPa at the highest sintering temperature.
[0049] In order to obtain a metal - matrix diamond composite material with high thermal conductivity, a pre - pressing process is adopted in combination with a special heating program and a pressure program to fix the positions of diamond particles, avoid the drift of diamond particles, and at the same time keep it warm at a certain temperature to remove the pressure - sensitive adhesive on the metal foil tape and reduce impurities.
[0050] Example 1
[0051] A method for preparing a shaped diamond - aluminum composite material with all - metal coating, as shown in the attached Figure 1 figures, the specific steps are as follows:
[0052] 1) Stamp an aluminum foil tape with a thickness of 0.1 mm into a circular sheet with a diameter of 50 mm.
[0053] 2) Use a cutting plotter to engrave the shape of the shaped part on the release paper, and tear off the release paper in the area of the shaped part.
[0054] 3) Use a diamond spreader to evenly spread diamond particles with a particle size of 100 μm (the coating on the diamond particles by vacuum evaporation coating method is TiC - Ti with a coating thickness of 0.02 μm) in the area of the shaped part on the aluminum foil tape. The diamond spreading in the shaped area of the aluminum foil tape is shown in Figure 2 the figures. Then tear off the release paper in the non - shaped part area, and use a spreader to evenly spread aluminum powder with a particle size of 70 μm on the whole aluminum foil tape to obtain a diamond - aluminum composite thin sheet.
[0055] 4) Stack multiple layers of the diamond - aluminum composite thin sheets and pre - press them with a hydraulic press at 10 MPa for 5 minutes to prepare a composite material preform with a thickness of 1.5 mm.
[0056] 5) Place the composite material preform in a hot - press furnace, evacuate to below 10 Pa, without applying pressure, increase the temperature to 500 °C at 5 °C / min and keep it warm for 1 hour to remove the glue, then apply pressure of 10 MPa, and then increase the temperature to 650 °C at 10 °C / min, apply pressure of 30 MPa, and keep it warm for 1 hour to obtain a composite material with a diamond - aluminum shaped part in the middle and aluminum on the top, bottom and around.
[0057] 6) Use laser cutting to cut out the diamond - aluminum shaped part from the whole composite material, rough - grind the shaped part, and then perform chemical - mechanical polishing to obtain a surface finish with Ra ≤ 0.4 μm and a thermal conductivity of TC = 340 (W·m -1 ·K-1 ) A diamond-aluminum shaped part with a coefficient of thermal expansion CTE = 6.5 (10 -6 / K), as shown in Figure 3 .
[0058] Example 2
[0059] A method for preparing a fully metal-clad diamond-copper composite with a special shape, the specific steps are as follows:
[0060] 1) Stamp a copper foil tape with a thickness of 0.08 mm into a circular sheet with a diameter of 100 mm;
[0061] 2) Use a cutting plotter to engrave the shape of the shaped part on the release paper, and tear off the release paper in the area of the shaped part;
[0062] 3) Use a diamond spreader to evenly spread diamond particles with a particle size of 100 μm (the coating on the diamond particles by vacuum evaporation coating method is WC-W, and the coating thickness is 0.01 μm) in the area of the shaped part in the copper foil tape, then tear off the release paper in the non-shaped part area, and use a spreader to evenly spread copper powder with a particle size of 80 μm on the whole copper foil tape to obtain a diamond-copper composite thin sheet;
[0063] 4) Stack multiple layers of the diamond-copper composite thin sheets and pre-press them with a hydraulic press at 20 MPa for 3 minutes to prepare a composite material preform;
[0064] 5) Place the composite material preform in a hot press furnace, evacuate to below 10 Pa, without applying pressure, heat it at 4 °C / min to 600 °C and keep it warm for 1 hour to remove the glue, then apply a pressure of 10 MPa, and then heat it at 10 °C / min to 1050 °C, apply a pressure of 40 MPa, and keep it warm for 30 minutes to obtain a composite material with a diamond-copper shaped part in the middle and copper on the top, bottom and around.
[0065] 6) Use electrical discharge machining to cut the diamond-copper shaped part out of the whole composite material, rough grind the shaped part, and then polish it by chemical mechanical polishing to obtain a diamond-copper shaped part with a surface finish Ra ≤ 0.4 μm, a thermal conductivity TC = 405 (W·m -1 ·K -1 ), and a coefficient of thermal expansion CTE = 7.6 (10 -6 / K). The cross-sectional micrograph of the diamond-copper shaped part prepared in Example 2 is shown in Figure 4 .
[0066] Example 3
[0067] A method for preparing a fully metal-clad diamond-copper composite with a special shape, the specific steps are as follows:
[0068] 1) Stamp a copper foil tape with a thickness of 0.1 mm into a circular sheet with a diameter of 100 mm;
[0069] 2) Use a cutting plotter to engrave the shape of the special-shaped part on the release paper, and tear off the release paper in the area of the special-shaped part;
[0070] 3) Use a diamond cloth applicator to evenly spread diamond particles with a particle size of 200 μm (the coating on the diamond particles is WC-W by vacuum evaporation coating method, and the coating thickness is 0.01 μm) in the area of the special-shaped part of the copper foil tape, then tear off the release paper in the non-special-shaped part area, and use a cloth applicator to evenly spread copper powder with a particle size of 80 μm on the whole copper foil tape to obtain a diamond-copper composite thin sheet;
[0071] 4) Stack multiple layers of the diamond-copper composite thin sheets and pre-press them with a hydraulic press at 10 MPa for 10 minutes to prepare a composite material preform;
[0072] 5) Place the composite material preform in a hot press furnace, evacuate to below 10 Pa, heat up to 500 °C at a rate of 2 °C / min and hold for 1 hour to remove the binder, then heat up to 1020 °C at a rate of 10 °C / min, apply a pressure of 50 MPa, and hold for 60 minutes to obtain a composite material with a diamond-copper special-shaped part in the middle and copper on the top, bottom, and around.
[0073] 6) Cut out the diamond-copper special-shaped part from the whole composite material by electrical discharge machining, rough grind the special-shaped part, and then perform chemical mechanical polishing to obtain a diamond-copper special-shaped part with a surface finish Ra≤0.4 μm, a thermal conductivity TC = 325 (W·m -1 ·K -1 ) and a coefficient of thermal expansion CTE = 7.9 (10 -6 / K).
[0074] Change the particle sizes of the diamond and aluminum powder in Example 1, and the results obtained through comparative tests are shown in Table 1.
[0075] Table 1
[0076]
[0077]
[0078] Change the hot pressing and sintering parameters in Example 1, and the results obtained through comparative tests are shown in Table 2.
[0079] Table 2
[0080]
[0081] It can be seen from the above comparison that inappropriate diamond particle size, metal powder particle size, low-temperature holding parameters, hot pressing and sintering temperature and pressure will all cause defects in the product, thereby affecting the performance.
[0082] All documents mentioned in this invention are cited herein by reference as if each individual document was cited by reference. In addition, it should be understood that after reading the above teachings of this invention, those skilled in the art can make various changes or modifications to this invention, and these equivalent forms also fall within the scope defined by the appended claims of this application.
Claims
1. A method for preparing a fully metal-clad special-shaped metal matrix diamond composite material, characterized in that it includes the following steps: (1) Use a cutting plotter to engrave the shapes of the cross-sections of the special-shaped parts on the release paper of the circular metal foil tape, and tear off the release paper in the area where the special-shaped parts are engraved; the metal foil tape consists of a metal base layer, a pressure-sensitive adhesive, and a release paper, with a thickness of 0.06 - 0.2 mm and a diameter of 10 - 500 mm, and the metal base layer is aluminum or copper with a purity higher than 99.95 wt%; (2) Use a diamond cloth spreader to evenly spread the diamond particles with a coating on the area of the special-shaped parts of the metal foil tape, then tear off the release paper in the non-special-shaped part area, and use a cloth spreader to evenly spread aluminum powder or copper powder on the metal foil tape to obtain a metal matrix diamond composite thin sheet; the diamond particles are artificial diamonds or natural diamonds, with a particle size of 40 - 500 μm; the particle size of the copper powder or aluminum powder is 20 - 300 μm; (3) Stack the obtained composite thin sheets in multiple layers and pre-press to obtain a preform of the metal matrix diamond composite material; (4) Place the obtained preform of the composite material in a hot press furnace, and hot press and sinter it into shape under a vacuum environment, and cut to obtain a fully metal-clad special-shaped metal matrix diamond composite material; when the preform of the composite material uses aluminum as the metal matrix, the hot press sintering process conditions are: the vacuum degree ≤ 10 Pa; the heating program is to heat up to 300 - 500 °C at a rate of 2 - 10 °C / min and hold for 0.5 - 2 h, then heat up to 600 - 750 °C at a rate of 5 - 20 °C / min and hold for 30 - 90 min; the pressure program is not to apply pressure before sintering, apply a pressure of 5 - 20 MPa at 500 - 600 °C, and apply a pressure of 5 - 50 MPa at the highest sintering temperature; When the preform of the composite material uses copper as the metal matrix, the hot press sintering process conditions are: the vacuum degree ≤ 10 Pa; the heating program is to heat up to 300 - 500 °C at a rate of 2 - 10 °C / min and hold for 0.5 - 2 h, then heat up to 850 - 1200 °C at a rate of 5 - 20 °C / min and hold for 30 - 90 min; the pressure program is not to apply pressure before sintering, apply a pressure of 5 - 20 MPa at 500 - 600 °C, and apply a pressure of 5 - 50 MPa at the highest sintering temperature.
2. The method for preparing a fully metal-clad special-shaped metal matrix diamond composite material according to claim 1, characterized in that the thickness of the metal foil tape described in step 1 is 0.08 - 0.15 mm, and the diameter is 80 - 200 mm.
3. The method for preparing a fully metal-clad special-shaped metal matrix diamond composite material according to claim 1, characterized in that in step 1, input the cross-sectional dimensions and shape information of the special-shaped parts into the cutting plotter through a computer to obtain the metal foil tape with the engraved shape of each cross-section.
4. The method for preparing a fully metal-clad special-shaped metal matrix diamond composite material according to claim 1, characterized in that the particle size of the diamond particles described in step 2 is 100 - 300 μm.
5. The method for preparing a fully metal-clad special-shaped metal matrix diamond composite material according to claim 1, characterized in that The coating described in Step 2 is one of SiC-Si, TiC-Ti, Cr 3 C 2 -Cr, WC-W prepared by vacuum evaporation coating method, and the coating thickness is 0.01~0.1μm.
6. The method for preparing a fully metal-clad special-shaped metal matrix diamond composite material according to claim 1, characterized in that The particle size of the copper powder or aluminum powder described in step 2 is 80 - 200 μm.
7. The preparation method of the all - metal - coated special - shaped metal - matrix diamond composite material as described in claim 1, characterized in that the pre - pressing pressure in step 3 is 5 - 50 MPa, the pressure - holding time is 1 - 10 min; the thickness of the pre - form is 0.2 - 5 mm.
8. The preparation method of the all - metal - coated special - shaped metal - matrix diamond composite material as described in claim 1, characterized in that the cutting described in step 4 is laser cutting or wire - cut electrical discharge machining; after cutting, it further includes rough grinding, fine grinding, and polishing of the special - shaped part to achieve a surface finish of Ra ≤ 0.4 μm.
Citation Information
Patent Citations
Easily processed diamond heat-conducting composite material and preparation method and application thereof
CN107649688A
Preparation method of insulating graphical high-thermal-conductivity diamond heat dissipation device
CN110482482A
Aluminum-based diamond composite material with high smoothness and preparation method thereof
CN114086016A